Sex differences in ocular biometric measurements: A twin study - Zhang, Han; Zhou, Jing; Yang, Lili; Zhang, Xiaogung; Shi, Wei; Yang, Hailong; Zhang, Guisen; She, Jie; Li, Huixia (Frontiers in Medicine, 2022)
Objective Gender differences in ocular biometric measurements of opposite-sex and same-sex twin pairs are still unclear. We aimed to investigate the difference between ocular biometric measurements in adolescent twin pairs. Materials and methods This retrospective study included a total of 64 eyes of 64 adolescents from 32 twins. The ocular biometric measurements and refractive prediction error (RE) were acquired from four groups of dizygotic (DZ) twins: boys from same-sex twin-pairs (SSM, n = 20), boys from opposite-sex twin-pairs (OSM, n = 8), girls from opposite-sex twin-pairs (OSF, n = 8), and girls from same-sex twin-pairs (SSF, n = 29). Results The mean age of the patient was 9.92 ± 2.84 (range: 6–18) years. Overall, boys had higher height, AL, WTW, but lower Ks, and Kf than girls (p < 0.05). Specifically, SSF was found to have the lowest lens thickness (LT), anterior chamber depth (ACD), central corneal thickness (CCT), white to white (WTW), and axial length (AL) levels, while the highest keratometry readings in the flat (Kf) and steep (Ks) levels compared with OSM, OSF, and SSM adolescents (p < 0.05). Compared with the OSF adolescents, ACD levels of the SSF adolescents were significantly lower [(2.99 ± 0.35) and (3.26 ± 0.15) mm, p = 0.033)], but Kf indicator was significantly larger [(43.93 ± 1.64) and (42.91 ± 1.75), p = 0.016)]. Conclusion Our study indicates that there was a significant difference in ocular biometric measurements between twin pairs, and sharing the uterus with a DZ twin SSF has smaller ocular indicator measurements. Our findings provide information on the eyeball and refractive development in adolescents.